Assessing knowledge, acts of discrimination, stigmatizing attitudes and its associated factors towards people living with HIV (PLHIV) among family medicine trainees in Malaysia - Chan, Hiang Ngee; Mohamad, Anuar; Abdul Rashid, Aneesa; Ho, Bee Kiau; Abdul Aziz Cooper, Alia; Mukhtar Aajamer, Haslina; Noor Emjah, Ermi; Krishnan, Jashithra Syamala; Hwee, Gloria Neo Lih (Academy of Family Physicians of Malaysia, 2022)
Introduction: Human immunodeficiency virus (HIV)-related stigmatisation and discrimination adversely affect health outcomes in terms of timely diagnosis, treatment and care. Despite global efforts, they remain common among healthcare workers worldwide. In Malaysia, family medicine specialists are entrusted with the care of HIV patients at the primary care level. This study aimed to assess HIV-related knowledge, acts of discrimination, stigmatising attitudes and their associated factors among family medicine trainees in Malaysia. Methodology: This cross-sectional study was conducted among 397 family medicine trainees in Malaysia using a validated, self-administered questionnaire that assessed the participants’ sociodemographic information, HIV/AIDS knowledge, stigmatising attitudes (attitudes of blame, attitudes towards imposed measures, comfort in dealing with HIV patients) and acts of discrimination. Results: The most common stigmatisation was “attitudes of blame” (mean [SD] score: 3.0 (0.74); range score:1–5), and the most frequent discriminatory act was breaching patient confidentiality (54.9%). Around 82.1% had good knowledge of HIV/AIDS. Married participants and participants who had 7 years or less in service were more stigmatising in “attitudes of imposed measures” towards people living with HIV (p=0.006). Conclusion: Family medicine trainees exhibited stigmatisation and discrimination towards HIV patients despite having good HIV knowledge. Hence, appropriate and concerted health education should be given to all family medicine trainees to eliminate stigmatisation and discrimination.